1987
DOI: 10.1161/01.cir.75.5.996
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamically important right ventricular infarction: follow-up evaluation of right ventricular systolic function at rest and during exercise with radionuclide ventriculography and respiratory gas exchange.

Abstract: The prognosis and recovery of right ventricular systolic function in patients with hemodynamically documented right ventricular myocardial infarction (RVMI) is unclear. Therefore 27 patients who met hemodynamic criteria for RVMI were followed for at least 1 year. Four patients died within 1 year and 23 survived. Postmortem examination performed in three of the four patients showed extensive infarction of the right and left ventricles. Survivors underwent early and late follow-up resting radionuclide ventriculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…One can estimate that at least 25% of the right ventricular cardiomyocytes are under the direct control of the EE; the remaining 75% will comprise the right ventricular compact myocardium, where they are under the control of the coronary perfusion and the MyoCapE. The substantial potential influence of the EE on right ventricular contractile performance may at least partly explain why considerably fewer cases of right ventricular dysfunction result from occlusion of the right coronary artery than there are of left ventricular dysfunction resulting from occlusion of the left coronary artery, and, why right ventricular function can improve remarkably after right ventricular infarction even in the absence of documented revascularization (112,113). Reperfusion of the right coronary artery will, obviously, enhance further recovery of right ventricular function, even after prolonged ischemia (49, 535).…”
Section: The Endothelial System: Conjectural Role Of Cardiac Endotmentioning
confidence: 99%
“…One can estimate that at least 25% of the right ventricular cardiomyocytes are under the direct control of the EE; the remaining 75% will comprise the right ventricular compact myocardium, where they are under the control of the coronary perfusion and the MyoCapE. The substantial potential influence of the EE on right ventricular contractile performance may at least partly explain why considerably fewer cases of right ventricular dysfunction result from occlusion of the right coronary artery than there are of left ventricular dysfunction resulting from occlusion of the left coronary artery, and, why right ventricular function can improve remarkably after right ventricular infarction even in the absence of documented revascularization (112,113). Reperfusion of the right coronary artery will, obviously, enhance further recovery of right ventricular function, even after prolonged ischemia (49, 535).…”
Section: The Endothelial System: Conjectural Role Of Cardiac Endotmentioning
confidence: 99%
“…Because the RV is thin walled and functions at low oxygen demands and low pressure with coronary perfusion throughout systole and diastole, extensive irreversible RV damage is unusual. 27 The prognosis of RV infarction is largely determined by the degree of associated LV infarction. 28 Volume therapy (200-1000 mL over the first several hours following the acute infarction) that has become standard on the basis of animal and human data 29 is only of benefit in the presence of low right atrial pressures.…”
Section: Treatment Of Rv Infarctionmentioning
confidence: 99%
“…These functional changes improved after the acute event [24] in some sub jects but not in others [25]. Even in subjects without myocardial infarction a decreased right ventricular ejec tion fraction has been noted on radionuclide angiogra phy [26], A correlation between hypokinesis, reduced ejection fraction and right ventricular dilatation at rest with electrocardiographic evidence of ST segment eleva tion in the V4R leads has been observed with nonin vasive techniques during acute myocardial infarction [11,24,26], and with hemodynamic studies as well [12], Croft et al [ 13] found that the sensitivity and specificity of electrocardiography was improved when V4R to V6R were employed in comparison to Vj, C4R or V4R alone (leads previously studied by others) [9-12, 24] during infarction.…”
Section: Limitations Of the Studymentioning
confidence: 99%